Friedreich's Ataxia with Retained Reflexes - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
Genetic linkage analyses in 11 patients from 6 families with Friedreich's ataxia (FA) phenotype, including cardiomyopathy, but retained reflexes (FARR), are reported from the University of Naples and C Besta Neurological Institute, Milan, Italy; and La Fe University Hospital, Spain.